Influence Of Organizational Culture And Environment Work On Job Satisfaction PT Garda Bhakti Nusantara - Willy Dwi Angga Putra; Saimara A.M Sebayang (Yayasan Multidimensi Kreatif, 2025)
The purpose of this study is to analyze how the company culture and physical workplace of PT Garda Bhakti Nusantara affect the level of employee happiness at work. Thirty-one staff members were sampled in the survey. The Likert scale questionnaire that has been evaluated and found to be reliable and valid is used as a data collection tool. Multiple linear regression is used in data analysis with the help of SPSS 19.0 software for Windows. The p-value of 0.000 for the organizational culture variable in this study shows that organizational culture has a positive and statistically significant influence on the level of job satisfaction among employees of PT Garda Bhakti Nusantar. With a p-value of 0.026, the Work Environment variable showed a negative and significant influence in the test findings. The impact of the work environment on employee job satisfaction at PT Garda Bhakti Nusantara is partly important. It can be concluded that the employee satisfaction of PT Garda Bhakti Nusantara is significantly influenced by the organizational culture and work environment, because the F value of 430,228 is greater than 3.34 and the significance value of 0.000 is less than 0.05. Thus, hypothesis 3 is acceptable and hypothesis 0 can be rejected.